Tafsir Sosial Perbedaan Gaya Hidup Remaja Muhammadiyah dan NU di Kota Semarang - Nugraha, Saka Mahardika Oktav Nugraha; Saka Mahardika Oktav Nugraha; Arum Ambarsari; Aris Septiono; Supriyanto (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2025)
Semarang City is where the pluralist Islamic teachings of two leading religious organizations in Indonesia, Muhammadiyah and Nahdlatul Ulama (NU), grow with their ideologies. What are the differences in interpreting social behaviour and the lifestyle of Muhammadiyah and NU youth in Semarang? The study used a qualitative phenomenological approach. According to Husserl (Creswell, 2009), phenomenological researchers reveal the basic meaning of invariant experiences and pressure on the intensity of consciousness. The study results show that the social interpretation of Muhammadiyah and NU youth regarding differences in social behaviour is correct and becomes a reference in everyday life. Differences in understanding of Fiqh between Muhammadiyah and NU youth are not obstacles to uniting society. NU youth can clash with NU youth, and Muhammadiyah youth can clash with Muhammadiyah youth because of differences in lifestyle.